Fuzzy Logic-Based For Predicting Roughness Performance Of Tiain Coating - Jaya, A. S. M; Mohd Hashim, Siti Zaiton; Abd Rahman, Md Nizam (2010)
In this paper a new application of fuzzy logic to predict the performance of Titanium Aluminum Nitride (TIAIN) sputtering coating process is presented. Titanium Aluminum Nitride (TiAlN) coated material is widely used as a cutting tool in machining due to its excellent properties such as hardness, roughness and wear. A fuzzy logic model was proposed to predict the coating roughness with respect to changes in input process parameters, the substrate sputtering power, bias voltage and temperature. Five membership functions are assigned to be associated with each input of the model. The predicted results obtained via fuzzy logic model were compared to the experimental result. The result indicated good agreement between the fuzzy model and experimental results with the 96.39% accuracy.